Humboldtia ponmudiana (Fabaceae-Detarioideae), a new species from Kerala, India - Santhosh Kumar, Ettickal Sukumaran; Shareef, Sainudeen Muhammed; Vikraman, Ramachandrakurup Raj (Phytotaxa, 2022)
Humboldtia ponmudiana (Fabaceae-Detarioideae), a new species from Kerala, is described here with photographs.  It is closely similar to H. decurrens, but differs in having black coloured bark, densely brown tomentose young shoots, lanceolate or ovate-lanceolate leaflets, sessile or subsessile flowers, large broadly ovate eglandular bracts, connate to middle bracteoles, 1-4 ovuled ovaries and silky tomentose pods with long beak. The IUCN conservation status, ecology, distribution along with a key to the species for the identification of the genus is also provided.